2004
DOI: 10.1186/1471-2385-4-1
|View full text |Cite
|
Sign up to set email alerts
|

188Re radiopharmaceuticals for radiosynovectomy: evaluation and comparison of tin colloid, hydroxyapatite and tin-ferric hydroxide macroaggregates

Abstract: Background: Radiosynovectomy is a therapy used to relieve pain and inflammation from rheumatoid arthritis and related diseases. In this study three 188 Re particulate compounds were characterized according to their physico-chemical properties and their biological behavior in rabbits. The results were compared in order to establish which was the radiopharmaceutical that better fits the requirements of this kind of radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
1
9
0
2
Order By: Relevance
“…Several candidates have been proposed to replace commercially available radiocolloid formulations of yttrium-90, rhenium-186 and erbium-169. These formulations include phosphorus-32 colloid [9,10], rhenium-186 sulphide [11], samarium-153 conjugated to particulate hydroxyapatite [12,13], dysprosium-165 ferric hydroxide [14,15], holmium-166 boromacroaggregates [16,17], ytterbium-175 and lutetium-177 hydroxyapatite [18,19]. In this study, the therapeutic efficacy of yttrium-90 citrate was compared to that of phosphorus-32 and rhenium-188 colloids.…”
Section: Discussionmentioning
confidence: 98%
“…Several candidates have been proposed to replace commercially available radiocolloid formulations of yttrium-90, rhenium-186 and erbium-169. These formulations include phosphorus-32 colloid [9,10], rhenium-186 sulphide [11], samarium-153 conjugated to particulate hydroxyapatite [12,13], dysprosium-165 ferric hydroxide [14,15], holmium-166 boromacroaggregates [16,17], ytterbium-175 and lutetium-177 hydroxyapatite [18,19]. In this study, the therapeutic efficacy of yttrium-90 citrate was compared to that of phosphorus-32 and rhenium-188 colloids.…”
Section: Discussionmentioning
confidence: 98%
“…[ 10 ] Study by Savio et al . [ 11 ] and Jeong et al . [ 12 ] concluded that Re-188 Sn colloid could be selected as the best formulation for synovectomy therapy taking into account ease of labeling procedure, kit formulation, minimum facilities required, suitable physical and biological characteristics, and the lowest absorbed dose for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…M41S-NH2 merupakan nanomaterial berpori yang tidak larut namun dapat terdistribusi secara merata dalam pelarut air sehingga merupakan radiofarmaka berbentuk koloid yang memang tidak dapat memisahkan pengotor dalam bentuk ReO2 sama seperti halnya TcO2 pada 99m Tc-Albumin HSA, 99m Tc-MAA dan 99m Tcmicrocoloid [23]. Oleh sebab itu dalam penentuan kemurnian radiokimia persentase pengotor yang diperhitungkan hanya pengotor 186 ReO4 [24][25][26] Sebagaimana obat umumnya, radiofarmaka yang masuk ke dalam tubuh, selain akan mengalami fase farmakokinetika melalui proses absorpsi, distribusi, metabolisme dan eliminasi, juga mengalami fase farmakodinamika yang melibatkan interaksi radiofarmaka dengan target tertentu seperti reseptor, transporter, enzim dan sebagainya [22]. Studi in vivo radiofarmaka dilakukan dengan cara uji biodistribusi untuk menentukan akumulasi radiofarmaka pada organ target dan pola penyebaran radiofarmaka di organ lainnya dalam tubuh.…”
Section: Hasil Dan Pembahasanunclassified
“…Data dari hasil uji biodistribusi memperlihatkan akumulasi radioaktivitas 186 Re-M41S-NH2 dilambung adalah sebesar 0,05% dan 0,14% (% ID) pada 3 dan 24 jam pasca injeksi yang menunjukkan radiofarmaka tersebut stabil secara in vivo. Data -data ini sesuai dengan beberapa partikel yang ditandai oleh radioisotop 188 Re untuk radiosinovektomi [24][25][26]. Hingga saat ini masalah utama penggunaan radiofarmaka bertanda partikel/koloid dalam terapi radiosinovektomi adalah adanya kebocoran (leakage) yang cukup besar dari radiofarmaka yang disuntikkan dimana ditemukan akumulasi yang tinggi di organ non target.…”
Section: Hasil Dan Pembahasanunclassified